Literature Review: Trauma Care for Psychological Strengthening of Adolescent Survivors of Sexual Violence - Darodjat, Ahmad Tubagus; Fajarianto, Otto; Pratiwi, Awalya Siska (Buletin Konseling Inovatif, 2026)
Sexual violence, both physically and psychologically, can be a traumatic stressor that triggers trauma in an individual's life. Trauma is a common condition that has a complex impact on an individual's life. This study aims to collect and analyze articles related to trauma care for psychological strengthening of adolescent survivors of sexual violence. The method used is a literature review. The author summarizes, makes a critical and in-depth analysis of previous literature. Based on the articles collected, it was found that sexual violence can leave a severe traumatic impact on victims. Victims may experience stress due to traumatic events, both during and after the event. Because of this condition, many victims of sexual violence are reluctant to report to the authorities because they feel unsafe, afraid of negative reactions, and embarrassed and intimidated by social stigma. They are worried that they will not be believed or even blamed, so they choose to keep their traumatic experiences without getting the support or justice they deserve. The role of media developers is to create applications that facilitate victims of sexual violence to report safely, anonymously, and easily. This application is designed to protect victims' privacy, reduce fear, and help them get support and justice without facing social stigma.